2016
DOI: 10.1186/s12978-016-0206-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcomes in pregnancies complicated by overweight and obesity

Abstract: BackgroundOverweight and obesity are associated with pregnancy complications and adverse perinatal outcomes, posing short and long-term risks for maternal and child health. This study evaluated maternal, delivery and neonatal outcomes in pregnancies complicated by overweight and obesity.MethodsThis prospective cross-sectional study included 258 pregnant women. According to prepregnancy body mass index (BMI), participants were classified as normal weight, overweight, or obese. Data were analyzed using the chi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 31 publications
3
31
1
8
Order By: Relevance
“…Requirement for insulin therapy, hypertensive disorders, preterm delivery, and caesarean sections were all more prevalent in women with pre-existing diabetes and early gestational diabetes. Maternal age and obesity are independent risk factors for adverse maternofetal outcomes including macrosomia and pregnancyrelated hypertensive disorders [10,11]. Significant variations existed in the mean age and prepregnancy BMI across the four groups in the Australian study.…”
Section: Discussionmentioning
confidence: 96%
“…Requirement for insulin therapy, hypertensive disorders, preterm delivery, and caesarean sections were all more prevalent in women with pre-existing diabetes and early gestational diabetes. Maternal age and obesity are independent risk factors for adverse maternofetal outcomes including macrosomia and pregnancyrelated hypertensive disorders [10,11]. Significant variations existed in the mean age and prepregnancy BMI across the four groups in the Australian study.…”
Section: Discussionmentioning
confidence: 96%
“…The causes of death were predominantly coronary heart disease, stroke and cancer [2]. In obese and overweight women, pregnancies and deliveries are more often associated with hypertension, preeclampsia and gestational diabetes, and higher frequency of infants that are large for gestational age [3]. These immediate complications of obesity are well known, but the long-term consequences for the health of these women are understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal obesity has been associated by with not only adverse outcomes for mothers and newborns but also to a need of additional obstetric interventions like IOL [41,42]. The current study revealed that there was a 12% an increased risk of IOL among obese women compared to those with normal BMI.…”
Section: Discussionmentioning
confidence: 52%